Implementación de un dispositivo electrónico de movimiento asistido para la ayuda a la movilidad de personas con discapacidad visual de la Unidad Educativa Especializada Dr. Luis Benavides - Medina Paz, José Alexander (2025)
Visual impairment limits independent mobility, and traditional tools such as the white cane offer only partial assistance, depending heavily on the environment and user experience. To address this issue, a low-cost portable electronic device was developed to improve the mobility of visually impaired individuals from the Specialized Educational Unit “Dr. Luis Benavides.” The implemented system uses a control board adapted from electric scooters to drive a brushless wheel motor, along with a gyroscope to regulate speed. Additionally, a custom PCB was designed, integrating HC-SR04 ultrasonic sensors to detect obstacles at distances of up to 30 cm, servomotors for directional movement, vibration motors for tactile alerts, and a DFPlayer Mini module to play voice messages. Preliminary results show that the device responds within 2 seconds to detected obstacles and improves travel time over 15 meters from 56 seconds (using a traditional cane) to 42 seconds. In conclusion, this technological proposal enhances user autonomy and provides a solid foundation for the development of new inclusive solutions.